2012
DOI: 10.1007/s00148-012-0425-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender patterns in Vietnam’s child mortality

Abstract: We analyze child mortality in Vietnam focusing on gender aspects. Contrary to several other countries in the region, mortality rates for boys are substantially larger than for girls. The mortality rate of boys appears to be more sensitive to parents' education levels than the mortality rate of girls. A high education level of the father is particularly protective for boys. The ruralurban mortality difference in the raw data, which is particularly large for boys, can be fully explained by differences in observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…More recently, because gender discrimination seems to be more evident in the age range of 1–4 years, the focus was moved to CMR and all under-five children. In some studies, the authors defined specific age groups for the analysis, reporting on non-standard age groups [ 5 , 7 , 24 , 36 , 37 , 39 , 46 , 54 , 72 – 74 , 78 , 80 , 81 , 83 , 85 , 86 , 88 90 , 94 , 99 , 101 , 108 , 110 , 111 , 114 , 115 , 117 , 118 , 126 , 128 , 139 , 146 , 149 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, because gender discrimination seems to be more evident in the age range of 1–4 years, the focus was moved to CMR and all under-five children. In some studies, the authors defined specific age groups for the analysis, reporting on non-standard age groups [ 5 , 7 , 24 , 36 , 37 , 39 , 46 , 54 , 72 – 74 , 78 , 80 , 81 , 83 , 85 , 86 , 88 90 , 94 , 99 , 101 , 108 , 110 , 111 , 114 , 115 , 117 , 118 , 126 , 128 , 139 , 146 , 149 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…A high education level of the father is particularly protective for boys. We have argued that gender-specific patterns of social interactions within the family could be a part of the explanation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nga et al identified the causes of neonatal death in Quang Ninh province and analysed this distribution by age at death, birth weight, and place of delivery from a clinical perspective ( 3 ). Pham et al investigated the patterns of child mortality by gender ( 4 ). They found that the mortality rate for boys was much higher than for girls and that this was associated with parents’ educational levels, in particular those of the father.…”
Section: Introductionmentioning
confidence: 99%